Designing innovation ecosystems for biointelligent value creation – Identification of promising technology fields and pioneer countries - Rentschler, Michael; Hohmann, Silja; Heuermann, Philipp; Valenti, Livio; Miehe, Robert (Journal of open innovation, 2025)
The concept of biointelligence as a convergence of life, information and engineering sciences was defined just over five years ago. Since then, several studies and scientific publications have dealt with the term and future implications of the topic. However, there has been a lack of a targeted and interdisciplinary approach to researching, developing, and designing biointelligent technologies, products, services, and business models. To implement the concept of biointelligence systematically and consistently, it is essential to examine which sub-areas of biointelligent value creation represent promising future markets and which countries and regions are potential pioneers. This article identifies hotspots in both dimensions and deduces where potential innovation ecosystems are located. To this end, comprehensive literature and database research were used to develop an indicator model to evaluate biointelligence innovation ecosystems. The result is the definition and delineation of 16 enabling technology fields, which divide the concept of biointelligent value creation into technological subject areas. Based on the data collected, our analysis results in a systematic derivation of five enabling technology fields assessed as particularly promising in connection with biointelligent value creation: smart greenhouses and smart farming, biorefineries and bioreactors, bio-computing and data storage, omics, as well as biosensors and bioactuators. Countries such as Israel, Finland, the USA, Canada, and Germany can be named pioneers in biointelligent value creation. Strong innovation ecosystems empower key stakeholders to partake in and incur the benefits of biointelligent value creation. This requires strategic and interdisciplinary partnerships between research institutions, governmental organizations and companies.